Efeito modulador do ômega-3 sobre a mutagenicidade e carcinogenicidade da Doxorrubicina em células somáticas de Drosophila melanogaster - Silva, Rosiane Gomes da (2011)
CHAPTER 2: Omega-3 (ω-3) is known for its actuation in the prevention and treatment of many kinds of colon, prostate, breast, and ovary cancer. ω-3 can be found in oily fishes with a high level of oil, such as sardine, salmon, codfish, as well as in vegetable oils, such as linseed, canola, soybeans, broccoli leaves and dark green leaves, such as spinach. The aim of this work was to evaluate the antimutagenic and antitumor proprieties of different ω-3 concentrations against the effect of the chemotherapic drug doxorubicin (DXR 0.125 mg/ml). To assess the mutagenicity of omega-3 use the SMART test (Somatic Mutation and Recombination Test) and assessment of carcinogenicity testing Warts for detection of epithelial tumors in Drosophila melanogaster, both in somatic cells of Drosophila melanogaster. The concentrations used in both experiments are: omega-3 (50 mg/ml, 100 mg/ml, 200 mg/ml) a positive control using doxorubicin(0.125 mg/ml) and a negative control using Twenn 80 of 1%. The SMART test results did not present a significant increase in the frequencies of mutant spots, when treated with only ω-3. However we observed a significant decrease in the frequencies of spots, in all the concentrations in which ω-3 was associated with the chemotherapic drug doxorubicin (DXR 0.125 mg/mL). In test for detection of epithelial tumor in Drosophila melanogaster, the results showed that there was no significant increase in the frequencies of tumors, when compared to the negative control. However there was a significant decrease in the frequency of tumors, in higher concentrations (100 and 200 mg/mL), when compared to the positive control. Under the experimental conditions proposed in this study, ω-3 showed antimutagenic activity modulating the effects induced by DXR. This modulating action on the DXR suggests the possibility of using the ω-3 as a chemopreventive.